Can communication media improve the KAP status of frontline health workers? A cross-sectional study on MCH indicators from Assam, India (South East Asia Journal of Public Health, 2016)
Frontline health workers are now key component in any public health delivery system, providing essential information on basic components of health, nutrition and sanitation for improving the utilization of primary health care delivery system by the community. This study was conducted to find out the Knowledge Attitude and Practices (KAP) of Accredited Social Health Activist (ASHA) workers on maternal health and child health components, service delivery system and to find out the association of different communication media on KAP status regarding above components. It is a cross-sectional study. Data was collected using a pre-tested structured questionnaire from 264 ASHA workers from 8 blocks of 5 districts of Assam selected randomly. Multiple regression analysis has been used to associate various findings and variables. The overall KAP status of most of the ASHAs (72%) was found to be 'Good'. It was observed that 70.45% had good KAP regarding maternal health components, 82.2% had good KAP on child health components, and 78.79% on common diseases. Communication media like TV, radio and mobile have also been found to have significant effect on certain KAP by ASHAs. Most of the ASHAs have been found competent in some aspects of health and nutrition components which have direct impact on child survival and maternal health. But at the same time average to poor knowledge level have been seen in some other important indicators. Hence proper training and timely re-orientation and information sharing through different suitable medium would be helpful for improving the KAP status of ASHAs.South East Asia Journal of Public Health Vol.5(2) 2015: 57-64